2016
DOI: 10.1111/jvp.12339
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic and pharmacodynamic properties of pergolide mesylate following long‐term administration to horses with pituitary pars intermedia dysfunction

Abstract: The objective of this study was to gain an understanding of the pharmacokinetic and pharmacodynamic properties of pergolide in horses with PPID after of long-term oral administration. Six horses with confirmed PPID were treated with pergolide (Prascend ) at 1 mg/horse po q24 h for 2 months, followed by 2 mg/horse po q24 h for 4 months. Following the last dose, plasma samples were collected for measurement of pergolide using an LC/MS/MS method and ACTH measurement using a chemiluminescent immunoassay. Noncompar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
1
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(46 citation statements)
references
References 19 publications
1
43
1
1
Order By: Relevance
“…Treatment with pergolide was strongly associated with survival. This finding is consistent with previous reports that established pergolide as the treatment of choice for PPID . In Australia, two forms of pergolide are approved for use in horses, a liquid form and a tablet form.…”
Section: Discussionsupporting
confidence: 92%
“…Treatment with pergolide was strongly associated with survival. This finding is consistent with previous reports that established pergolide as the treatment of choice for PPID . In Australia, two forms of pergolide are approved for use in horses, a liquid form and a tablet form.…”
Section: Discussionsupporting
confidence: 92%
“…The dose of pergolide should be increased until clinical signs have greatly improved and test results have at least dramatically improved or ideally normalised. Daily dosing is recommended because the half‐life ranged from 5.6 to 60 h in a single‐dose study, and was approximately 24 h in a chronic‐dosing study . In the chronic‐dosing study, six horses with confirmed PPID were administered pergolide at 0.002 mg/kg PO every 24 h for 2 months, followed by 0.004 mg/kg PO every 24 h for an additional 4 months.…”
Section: Treatmentmentioning
confidence: 99%
“…Daily dosing is recommended because the half‐life ranged from 5.6 to 60 h in a single‐dose study, and was approximately 24 h in a chronic‐dosing study . In the chronic‐dosing study, six horses with confirmed PPID were administered pergolide at 0.002 mg/kg PO every 24 h for 2 months, followed by 0.004 mg/kg PO every 24 h for an additional 4 months. Plasma ACTH concentration increased by 50% in three of the six horses 2 days after the last dose and in all six horses by 10 days after the last dose.…”
Section: Treatmentmentioning
confidence: 99%
See 2 more Smart Citations